Study of suitability waters location for seaweed culture in Muna Regency, Indonesia - Sitti Sasrani Mutrono Gufana; Fendi Fendi; Karyawati Karyawati; Abbas Sommeng (Sekolah Tinggi Ilmu Pertanian Wuna, 2017)
The research aims to determine the location of cultivation at various levels of suitability and identify physical and chemical conditions in the location of seaweed cultivation in the Muna Regency. The study was conducted in June 2018 in 4 (four) stations which are coastal areas of Muna Regency, namely Marobo Village Marobo District (Station 1), Komba-Komba Village Kabangka District (Station 2), Lasunapa Village Duruka District (Station 3), and Bahari Village Towea District (Station 4). Observation and measurement and sampling were carried out at three different locations, namely observation point 1 (a location that was never planted seaweed), observation point 2 (former location of seaweed cultivation), and observation point 3 (location of seaweed cultivation). The results showed that the location of waters for seaweed cultivation in the Muna Regency consisted of appropriate and less appropriate criteria based on the value of the evaluation results of the suitability of the location of waters for seaweed cultivation. These criteria are scattered at each station's observation points. All physical and chemical parameters of the waters in the land suitability criteria become a limiting factor for seaweed growth, at each observation point that is different at each station. All types of seaweed (algae) can live in the waters of Muna Regency, where seaweed species Eucheuma cottonii, Eucheuma spinosum, and Gracilaria sp. are types that are already common in cultivation, and Eucheuma cottonii and Eucheuma spinosum are types that are already popular in seaweed cultivation activists in Muna Regency